Argentina - Income Support Policies towards the Bicentennial - Rofman, Rafael (World Bank, Washington, DC, 2012)
As Argentina approaches its bicentennial as an independent republic, it has a window of opportunity in social protection policy. As growth has returned and social indicators have recovered to pre-2001/2002 crisis levels, there is an opening to move from emergency income support programs to a more comprehensive, long-term and sustainable strategy for social protection. A recent report aims to contribute to the discussion of options for social protection. Specifically, it focuses on non-contributory income support in Argentina through discussion of the current set of programs, their coverage, effectiveness, costs and sustainability. It looks at the potential impact of the government's new social protection programs - Seguro de Capacitacion y Empleo and Familias - which are in the early stages of being rolled-out and specifically at the institutional set-up for social protection and the potential role of provinces in Argentina's federal system. The report focused on income support in Argentina. The work was carried out between July 2006 and June 2008 by a World Bank team in collaboration with a wide range of partners in Argentina.